2006
DOI: 10.2353/ajpath.2006.041089
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Inhibitors Suppress Transforming Growth Factor-β-Induced Subcapsular Cataract Formation

Abstract: The pleotropic morphogen transforming growth factor-beta (TGFbeta) plays an important role in the development of fibrotic pathologies, including anterior subcapsular cataracts (ASCs). ASC formation involves increased proliferation and transition of lens epithelial cells into myofibroblasts, through epithelial-mesenchymal transformation that results in opaque plaques beneath the lens capsule. In this study, we used a previously established TGFbeta-induced rat cataract model to explore the role of matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…Indeed, active TGF-b1 can induce transdifferentiation from fibroblasts to myofibroblasts in the tumour microenvironment, which show an increased expression of various proteolytic enzymes including MMPs (Dwivedi et al, 2006). In turn, these proteases, including plasmin (George et al, 2005), MMP-2 (Wang et al, 2006), MMP-3 (Maeda et al, 2002) and MMP-13 (D'Angelo et al, 2001), have been shown to be involved in TGF-b1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, active TGF-b1 can induce transdifferentiation from fibroblasts to myofibroblasts in the tumour microenvironment, which show an increased expression of various proteolytic enzymes including MMPs (Dwivedi et al, 2006). In turn, these proteases, including plasmin (George et al, 2005), MMP-2 (Wang et al, 2006), MMP-3 (Maeda et al, 2002) and MMP-13 (D'Angelo et al, 2001), have been shown to be involved in TGF-b1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in both murine mammary epithelium and a rat cataract model, E-cadherin ectodomain shedding was found to promote an EMT (18,51). Although the association between EMT and E-cadherin ectodomain shedding has not been extensively evaluated in human cancer models, sE-cad is elevated in the bodily fluids of cancer patients and is associated with poor prognosis or the development of metastasis (12,13,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TGF␤ has also been implicated in multiple fibrotic diseases, including those of the eye, such as glaucoma and anterior subcapsular cataract (35)(36)(37)(38). Moreover, several mechanisms of TGF␤ activation are known (39), and a diverse…”
mentioning
confidence: 99%